Strategy for Using Technology (E-Learning) to Support Indonesian Language Learning - Sihite, Eny; Sidabutar, Hikmah; Lumbantoruan, Rotua; Siregar, Rosdiana; Tansliova, Lili (QISTINA: Jurnal Multidisiplin Indonesia, 2024)
This article discusses strategies for using technology, especially e-learning, to support Indonesian language learning. With advances in information and communication technology, e-learning has become a potential approach to the learning process in various fields, including Indonesian. This research outlines various strategies that can be applied in the use of e-learning to increase the effectiveness of Indonesian language learning. Various aspects discussed include the use of e-learning platforms, appropriate learning design, multimedia integration, interactivity, and learning assessment. This article also presents case studies or examples of the use of e-learning technology in the context of Indonesian language learning. In conclusion, the integration of e-learning technology with Indonesian language learning has great potential to increase learning motivation, student engagement and learning outcomes. This means that this approach can be an effective means of enriching and expanding the Indonesian language learning experience in the current digital era.